2014
DOI: 10.1177/1741143214543200
|View full text |Cite
|
Sign up to set email alerts
|

Gendered trends in student teachers’ professional aspirations

Abstract: The paper reports on a small-scale, exploratory study investigating the professional aspirations of a cohort of student teachers at a UK university. Questionnaires and interviews sought insights into the students' perceptions of leadership, future aspirations and selfperceptions as potential leaders. Whilst there was commonality in male and female students' interest in subject-leadership and teaching-and learning-oriented roles such as Advanced Skills Teacher, gendered trends emerged in patterns of aspiration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 49 publications
0
8
1
Order By: Relevance
“…The participants' spouses valued their career accomplishments and were willing to make the necessary adjustments to their family life to facilitate it. This was contrary to the findings of the majority of the extant Western literature, which suggested that having children is a barrier to women's career progression and that in many cases, women prefer to remain single if they intend to pursue leadership roles (Eddy, 2009;Smith, 2015). The present study challenged this assumption, revealing that women's families play a crucial role in constructing their identity in family-oriented cultures, providing practical support, helping with childcare, and encouraging them to advance their careers in a patriarchal work environment.…”
Section: Family Supportcontrasting
confidence: 78%
See 1 more Smart Citation
“…The participants' spouses valued their career accomplishments and were willing to make the necessary adjustments to their family life to facilitate it. This was contrary to the findings of the majority of the extant Western literature, which suggested that having children is a barrier to women's career progression and that in many cases, women prefer to remain single if they intend to pursue leadership roles (Eddy, 2009;Smith, 2015). The present study challenged this assumption, revealing that women's families play a crucial role in constructing their identity in family-oriented cultures, providing practical support, helping with childcare, and encouraging them to advance their careers in a patriarchal work environment.…”
Section: Family Supportcontrasting
confidence: 78%
“…The investigation confirmed the findings of the existing research concerning the positive effect of societal factors and personal traits, both internal and external, that empowered and boosted the participants' careers in academia. As expected, the perception of the participants differed from that commonly reported regarding women in leadership positions, which assumed that single women could progress more rapidly up the career ladder than women with families (Eddy, 2009;Smith, 2015). On the contrary, in collective societies where the concept of marriage is powerful, being married affects women's social status positively, and their chances of accessing leadership are much higher (Al-Abri, 2010).…”
Section: Discussionmentioning
confidence: 82%
“…For example, Smith (2012) reported that a third of secondary headships were held by women in England and Wales. Based on questionnaires and interviews, she described the differences of female and male student teachers' professional aspirations at a UK university (Smith, 2014). Whilst there was commonality in interest in subject leadership and teaching-and learning-oriented roles such as Advanced Skills Teacher, women were more likely than men to aspire to the post of Special Educational Needs Coordinator, and men were more likely to aspire to the most senior posts, especially headship.…”
Section: Gender Portrayed In Teachers' Storiesmentioning
confidence: 99%
“…Whilst both showed awareness of the challenging aspects of management, men were more likely to perceive the advantages and to envisage themselves as headteachers. There was also a difference in the ways in which men and women constructed teaching and leadership (Smith, 2014). Smith (2012), using life history interviews with 40 secondary school female teachers in all stages of their professional careers in the UK, looked at the main factors affecting their career decisions and drew up a typology of female teachers' approaches to career, identifying two types: those who defined their teaching career as self-defined and planned, and those who saw their career paths as defined by external factors, where the circumstances of their lives and jobs (available opportunities, limitations, level of support from others, fate, chance events, family responsibilities, partner's attitude, and so on) framed their decisions, and in some cases, stymied their potential progress (Smith, 2012).…”
Section: Gender Portrayed In Teachers' Storiesmentioning
confidence: 99%
“…A subsequent study focusing on the aspirations of a cohort of student teachers (Smith 2015) found that men were far more likely than women to aspire to headship. Even before embarking upon their teaching careers the majority of the women in the study (and some of the men) did not consider headship to be a career option for them.…”
Section: Introductionmentioning
confidence: 99%